Porcine collagen matrix for treating gingival recession. Randomized clinical trial. - Yuri Castro; Sixto Grados (Universidad de Concepción., 2014)
Achieving root coverage after exposure caused by gingival recession is one of the main goals of reconstructive periodontal surgery. Even though a large variety of techniques and mucogingival grafting procedures are available, their long-term results are not clear yet. Therefore, this study aimed to compare clinical effectiveness of the porcine collagen matrix with subepithelial connective graft for treating Miller class I and II gingival recessions. Materials and methods: The randomized clinical trial included twelve patients assigned to two groups. In the first group (experimental), six patients were treated using collagen matrix (mean age, 54.3±5.6 years; mean recession 2. 67±1.03mm). Another group (control) of six patients was treated using connective grafts (mean age, 57.1± 2.7 years; mean recession 4.33±1.03mm). All patients underwent periodontal evaluation and pre-surgical preparation including oral hygiene instruction and supragingival scaling. Gingival recessions were exposed through partial thickness flaps where the grafts and matrices were placed. Patients were assessed periodically until complete healing of tissue. Results: Root coverage parameters, amount of keratinized gingiva, gingival biotype and clinical attachment level were evaluated. The root coverage percentage for the group using connective graft was 24.7±13.5% and 16.6±26.8% for the one treated with the matrix. The amount of increased keratinized tissue was 4.33±2.06mm and 4.5±0.83mm for the control and experimental group respectively. Both groups increased gingival biotypes from thin to thick at 100%. The final clinical attachment level was 4.17±3.17±04mm for the control group and 0.98mm for the experimental group. There were significant differences between the outcome of gingival recession and clinical attachment. Conclusion: Results indicate both techniques, besides being predictable, are useful for improving clinical parameters when treating gingival recessions. Regardless of the fact that better root coverage was obtained with the subepithelial connective graft, both methods are really useful for increasing the thickness of keratinized tissue.